Prolonged-release fampridine for the treatment of myoclonus after cervical myelitis: a case report - Mona Klara Ros Müller; Monika Christ; Markus Naumann; Antonios Bayas (Therapeutic Advances in Neurological Disorders, 2022)
Prolonged-release fampridine (PR-FAM), a potassium channel blocker, is approved for improving walking ability in patients with multiple sclerosis (MS). Beyond this, positive effects on other MS symptoms like fatigue, cognition, and tremor have been described. To our knowledge, a positive effect of PR-FAM on spinal myoclonus has not been described so far. Here, we report a 32-year-old female with myoclonus after cervical myelitis affecting both hands which markedly improved after administration of PR-FAM. Treatments used before such as carbamazepine or levetiracetam had to be withdrawn because of intolerable side effects or lack of efficacy. The positive effect of PR-FAM could be confirmed by transient suspension. PR-FAM may be considered as a treatment option in refractory spinal myoclonus after myelitis in selected cases.